Lasers in dentistry : guide for clinical practice - Freitas, Patricia M. de; Simoes, Alyne (Ames, Iowa : Wiley Blackwell, 2015)
'Lasers have become an increasingly useful tool in conventional dental practice. Their precision and less invasive quality make them an attractive technology in esthetic and pediatric dentistry, oral medicine, and a range of other dental procedures. Lasers in Dentistry: Guide for Clinical Practice is a comprehensive, yet concise and easy-to-use guide to integrating lasers into conventional clinical practice.The book begins by providing the reader a thorough understanding of how lasers work and their varied effects on oral tissues. Subsequent chapters are organized by procedure type, illustrating common clinical techniques with step-by-step illustrations and case examples. In addition, each chapter provides an overview of the latest research for use in clinical practice. More comprehensive than at atlas yet practical and clinically oriented in its approach, Lasers in Dentistry is an essential tool for practitioners and students looking to broader their skill set in laser dentistry'--Provided by publisher.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Laser Therapy -- methods; Oral Surgical Procedures -- instrumentation; Dentistry -- methods; Stomatognathic Diseases -- therapy; Lasers in dentistry; Dentistry, Operative; MEDICAL / Surgery / General; Dentistry, Operative; Lasers in dentistry; Medical; Electronic books